A composite durable antistatic gas isolation system and construction method

By combining the sprayed initial lining concrete structure, anti-static polyethylene closed-cell foam plate and isolation plate with airtightener in the gas tunnel, the safety hazards of gas gas escape are solved and the safety and operation of gas tunnels are improved. Risk, gas isolation and flame retardancy are achieved.

CN111594222BActive Publication Date: 2025-01-14SICHUAN WEIDUN NEW MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202010475375.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-05-29
Publication Date
2025-01-14
Estimated Expiration
2040-05-29

AI Technical Summary

Technical Problem

In the prior art, only gas isolation plates are used to block gas gas, which poses a safety hazard for gas gas escape, resulting in high risk of gas tunnel operation.

Method used

Adopt composite durable antistatic gas isolation system, including sprayed initial lining concrete structure with airtight agent, antistatic polyethylene closed-cell foam board and isolation board, combined with airtight agent secondary lining concrete structure, through high conductive carbon black Materials such as flame retardants improve the barrier properties of gas gas.

Benefits of technology

It effectively avoids gas gas escape, improves the safety of gas tunnels, meets gas isolation, flame retardancy, antistatic properties and excellent mechanical properties, extends the service life of the material, and reduces operational risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111594222B_ABST
    Figure CN111594222B_ABST
Patent Text Reader

Abstract

The present invention provides a composite durable antistatic gas isolation system and construction method, which solves the problem that the prior art only uses gas isolation plates to block gas, which has the potential safety hazard of gas gas escaping easily and the technical problem of high risk in gas tunnel operation. It comprises a primary lining concrete structure mixed with air sealant, an antistatic polyethylene closed-cell foam board, an isolation plate, and a secondary lining concrete structure mixed with air sealant in sequence; wherein the primary lining concrete structure mixed with air sealant is arranged on the side close to the gas. The present invention can meet the requirements of gas isolation, flame retardancy, antistatic properties and excellent mechanical properties, can avoid gas gas escape as much as possible, and improve the safety of gas tunnel engineering operation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite durable antistatic gas isolation system and a construction method. Background Art

[0002] The anti-gas and waterproof isolation projects in my country's tunnels mainly need to meet the requirements of gas isolation, flame retardancy, anti-static properties and excellent mechanical properties. The current technology considers gas isolation panels for isolation more, without considering the role of concrete on both sides. In fact, the concrete structure itself plays a huge role in blocking gas, but it has been overlooked. During long-term use, gas has diffused to the inside of the tunnel. As the concentration increases, accidents occur, and the operating risk of gas tunnels increases.

[0003] Therefore, the constructed tunnel gas isolation system is the key technology to solve the gas leakage in gas tunnels.

[0004] The applicant has found that the prior art has at least the following technical problems:

[0005] In the prior art, only gas isolation plates are used to block gas, which has the potential safety hazard that gas is easy to escape, and there is a technical problem of high risk in gas tunnel operation. Summary of the invention

[0006] The purpose of the present invention is to provide a composite durable antistatic gas isolation system and construction method to solve the technical problems that the prior art only uses gas isolation plates to block gas, which has the potential safety hazards of gas escape and the high risk of gas tunnel operation. The preferred technical solutions among the many technical solutions provided by the present invention can produce many technical effects as described below.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides a composite durable antistatic gas isolation system, which comprises a primary lining concrete structure mixed with air sealant, an antistatic polyethylene closed-cell foam board, an isolation board, and a secondary lining concrete structure mixed with air sealant in sequence; wherein the sprayed primary lining concrete structure mixed with air sealant is arranged on a side close to the gas;

[0009] The antistatic polyethylene closed-cell foam board is prepared from the following raw materials in percentage by weight:

[0010] Linear low-density polyethylene 70.7%-85.6%;

[0011] Highly conductive carbon black 5%-10%;

[0012] High-density polyethylene 5%-10%;

[0013] Foaming agent 1%-2%;

[0014] Crosslinking agent 1%-2%;

[0015] Dispersant 0.3%-0.8%;

[0016] Coupling agent 0.1%-0.5%;

[0017] Stabilizer 0.5%-1%;

[0018] Antioxidant 1%-1.5%;

[0019] Anti-ultraviolet agent 0.5%-1.5%;

[0020] The sum of the weight percentages of the various raw materials is 100%.

[0021] Furthermore, the raw materials for preparing the antistatic polyethylene closed-cell foam board include:

[0022] The foaming agent is azodicarbonamide;

[0023] The cross-linking agent is DCP;

[0024] The dispersant is vinyl bisstearamide;

[0025] The coupling agent is a silane coupling agent;

[0026] The antioxidant comprises the following raw materials in parts by weight: 0.5 to 1 part of tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentyl alcohol; 0.5 part of tris(2,4-di-tert-butylphenyl) phosphite;

[0027] The anti-ultraviolet agent comprises the following raw materials in parts by weight: ultraviolet absorber: 0.2-0.7 parts; hindered amine light stabilizer: 0.3-0.8 parts.

[0028] Furthermore, the method for preparing the antistatic polyethylene closed-cell foam board comprises the following steps:

[0029] (1) Preliminary mixing of solid materials: linear low-density polyethylene, high-conductive carbon black, high-density polyethylene, and foaming agent are weighed according to the proportion and put into a mixer for the first preliminary mixing. The materials are mixed at a temperature of 45°C-55°C for 4-6 minutes until they are uniformly mixed;

[0030] (2) Blending of additives: After weighing the coupling agent, cross-linking agent, dispersant, stabilizer, antioxidant and anti-ultraviolet agent according to the proportion, add them into the mixer for secondary blending, and mix them at a temperature of 45°C-55°C for 8min-12min until they are uniformly mixed to obtain a uniformly mixed formula material;

[0031] (3) Extrusion molding: The uniformly mixed formula material in step (2) is conveyed into a twin-screw through a twin-screw spiral riser, and an antistatic polyethylene closed-cell foam sheet is extruded at an extrusion temperature of 190° C. to 210° C., and then a three-roll molding machine is used to set the thickness and then cooled to room temperature;

[0032] (4) Coil winding: The antistatic polyethylene closed-cell foam board after corona treatment is dried and cooled, and then pulled and rolled.

[0033] Furthermore, the isolation board is a gas isolation board or a non-asphalt-based self-adhesive gas isolation board; wherein,

[0034] The permeability coefficient of the gas isolation board is ≤1×10 -15 cm 3 cm / cm 2 ·s·Pa;

[0035] The air permeability coefficient of the non-asphalt-based self-adhesive gas isolation board is ≤1×10 -16 cm 3 cm / cm 2 ·s·Pa.

[0036] Furthermore, the non-asphalt-based self-adhesive gas isolation board includes a polymer waterproof board layer, a self-adhesive layer and a polyurethane coating layer; the polymer waterproof board layer is the bottom layer, the self-adhesive layer covers the polymer waterproof board layer, and the polyurethane coating layer is the surface layer.

[0037] Furthermore, the polymer waterproof board in the polymer waterproof board layer is prepared from the following raw materials in weight percentage:

[0038] Linear low density polyethylene 25%-50%

[0039] Nylon 6 / EVOH 10%-30%

[0040] High-density polyethylene 5%-10%;

[0041] Toughener 5%-15%;

[0042] Flame retardant 10%-20%;

[0043] Compatibilizer 1%-6%;

[0044] Modification additives 1%-2%;

[0045] Antioxidant 1%-1.5%;

[0046] Anti-ultraviolet agent 0.5%-1.5%;

[0047] The sum of the weight percentages of the various raw materials is 100%.

[0048] Furthermore, the self-adhesive material in the self-adhesive material layer is prepared from the following raw materials in weight percentage:

[0049] SIS elastomer 18%-21%;

[0050] First polyisobutylene 10%-18%;

[0051] Second polyisobutylene 6%-8%;

[0052] First, C5 petroleum resin 25%-30%;

[0053] The second C5 petroleum resin 5%-12%;

[0054] Flame retardant 10%-20%;

[0055] Polyethylene wax 2%-5%;

[0056] Antioxidant 1%-1.5%;

[0057] Anti-ultraviolet agent 0.5%-1.5%;

[0058] The sum of the weight percentages of each raw material is 100%;

[0059] in,

[0060] The first polyisobutylene is a low molecular weight polyisobutylene;

[0061] The second polyisobutylene is a high molecular weight polyisobutylene;

[0062] The first C5 petroleum resin is aliphatic C5;

[0063] The second C5 petroleum resin is an aliphatic C5 hydrogenated petroleum resin.

[0064] Furthermore, the raw materials for preparing the polymer waterproof board include:

[0065] The vinyl molar equivalent content in the nylon 6 / EVOH barrier material is not less than 44%, and the weight ratio of nylon to EVOH is 5:5;

[0066] The toughening agent comprises the following raw materials in parts by weight: 5-10 parts of polyolefin thermoplastic elastomer; 0-5 parts of thermoplastic ethylene-propylene rubber;

[0067] The flame retardant is a nitrogen-phosphorus halogen-free environmentally friendly flame retardant;

[0068] The compatibilizer is a maleic anhydride type grafting agent;

[0069] The modification aid comprises the following raw materials in parts by weight: polyethylene wax: 0.5-1 part; vinyl bisstearamide: 0.3-0.8 part; white oil: 0.2 part;

[0070] The antioxidant comprises the following raw materials in parts by weight: 0.5 to 1 part of tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentyl alcohol; 0.5 part of tris(2,4-di-tert-butylphenyl) phosphite;

[0071] The anti-ultraviolet agent comprises the following raw materials in parts by weight: ultraviolet absorber: 0.2-0.7 parts; hindered amine light stabilizer: 0.3-0.8 parts;

[0072] The raw materials for preparing the self-adhesive material include:

[0073] The flame retardant is a nitrogen-phosphorus halogen-free environmentally friendly flame retardant;

[0074] The toughening agent includes the following raw materials in parts by weight: The antioxidant includes the following raw materials in parts by weight: 0.5 to 1 part of tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentyl alcohol; 0.5 part of tris(2,4-di-tert-butylphenyl) phosphite;

[0075] The anti-ultraviolet agent comprises the following raw materials in parts by weight: ultraviolet absorber: 0.2-0.7 parts; hindered amine light stabilizer: 0.3-0.8 parts.

[0076] Furthermore, the method for preparing the non-asphalt-based self-adhesive gas isolation board comprises the following steps:

[0077] S1. Preparation of polymer waterproof board:

[0078] A1. Raw material premixing: All raw materials are sucked into the high-speed mixer through a vacuum pump according to the proportion, and then dried in the high-speed mixer for 2-4 minutes. Then, the raw materials are put into the low-speed mixer for 4-6 minutes until the raw materials are evenly mixed.

[0079] A2, extrusion molding: the raw materials mixed evenly in step A1 are conveyed into a twin-screw extruder through a double-screw conveyor, and the polymer waterproof board is extruded at an extrusion temperature of 220°C-240°C, and then the thickness is determined by a three-roll molding machine (the polymer waterproof board has a variety of specifications, generally the thickness is 1.5mm, 2.0mm, 2.5mm, 3.0mm, and can also be customized according to customer requirements) and then cooled to room temperature after molding;

[0080] A3, internal stress treatment: the polymer waterproof sheet formed in step A2 is pulled through the traction roller to the internal stress treatment section, and is circulated through 4 groups of 80°C high-temperature rollers and 4 groups of 10°C low-temperature rollers for 3-5 times to treat and shape the sheet and eliminate the internal stress in the sheet;

[0081] A4, corona treatment: Place both ends of the polymer waterproof board after internal stress treatment in A2 under 7KV voltage for corona treatment, forming oxidized polarization groups on the surface of the polymer waterproof board, so that the surface of the waterproof board produces polarity;

[0082] A5. Coil rolling: The polymer waterproof board with internal stress eliminated in step A3 is dried, cooled, pulled and rolled up to obtain a finished polymer waterproof board;

[0083] S2. Preparation of self-adhesive material:

[0084] B1. Liquid material feeding: weigh the first polyisobutylene, the first C5 petroleum resin and the second C5 petroleum resin according to the ratio and put them into the reactor, and stir them at a high speed at a temperature of 90°C-110°C for 18min-25min until they are evenly mixed;

[0085] B2. Solid material feeding: SIS elastomer, second polyisobutylene, flame retardant, polyethylene wax, antioxidant and anti-ultraviolet agent are weighed according to the proportion and put into the reaction kettle under high-speed stirring, and the temperature is raised to 150-170°C at the same time. After the temperature rises to 150-170°C, continue stirring for 35-45 minutes to obtain hot melt adhesive;

[0086] B3, discharging and molding: after the hot melt adhesive prepared in step B2 passes through a filter screen, a self-adhesive finished product in the state of hot melt adhesive is obtained, and the finished product is put into a packaging bag;

[0087] S3. Apply the self-adhesive material to the polymer waterproof board:

[0088] C1. Hot melt box heating: put the hot melt adhesive in the packaging bag into the hot melt box, heat and melt it through a step heating process of 155℃-170℃ to obtain molten adhesive;

[0089] C2, coating die coating: the molten adhesive in step C3 is conveyed to the coating die of the hot melt box through the conveying channel in the hot melt box, and is evenly coated on the polymer waterproof board prepared in step S1 at a die temperature of 150° C., that is, a self-adhesive layer is formed on the polymer waterproof board layer;

[0090] S4. Applying polyurethane coating layer:

[0091] D1. Spray coating: Spray the polyurethane coating layer on the self-adhesive layer with a spray thickness of 0.15mm-0.2mm;

[0092] D2. Drying: Dry the polymer waterproof board sprayed with polyurethane coating in step D1 at a temperature of 55° C.-65° C. for 4.5 min-5.5 min to obtain a finished product of a non-asphalt-based self-adhesive gas isolation board.

[0093] The method for constructing a composite durable antistatic gas isolation system provided by the present invention comprises the following steps:

[0094] (1) Spraying the primary lining concrete structure on the rock protection structure, the thickness of the primary lining concrete structure is 10cm-15cm;

[0095] (2) Gluing antistatic polyethylene closed-cell foam board to the primary lining concrete structure;

[0096] (3) Use the suspension method or concealed nailing ring to fix the isolation board on the antistatic polyethylene closed-cell foam board;

[0097] In the isolation board: the thickness of the polymer waterproof board layer is 1.2mm-2.0mm; the thickness of the self-adhesive layer is 0.3mm-0.8mm; the thickness of the polyurethane coating layer is 0.15mm-0.2mm;

[0098] (4) A secondary lining concrete structure is sprayed on the isolation board, and the thickness of the secondary lining concrete structure is 40cm-50cm.

[0099] Based on the above technical solution, the embodiments of the present invention can at least produce the following technical effects:

[0100] The composite durable antistatic gas isolation system provided by the present invention is composed of a sprayed primary lining concrete structure mixed with air sealant, an antistatic polyethylene closed-cell foam board, an isolation board and a secondary lining concrete structure mixed with air sealant; not only the antistatic polyethylene closed-cell foam board and the isolation board can form a barrier to gas, but the sprayed primary lining concrete structure mixed with air sealant and the secondary lining concrete structure mixed with air sealant can also form a barrier to gas, which can avoid gas escape as much as possible and improve the safety of gas tunnel engineering operation; the composite durable antistatic gas isolation system provided by the present invention can meet the requirements of gas isolation, flame retardancy, antistatic properties and excellent mechanical properties, specifically:

[0101] ① The polymer waterproof board in the composite durable antistatic gas isolation system provided by the present invention adopts linear low-density polyethylene which can provide excellent elongation and construction performance; the high-density polyethylene adopted can improve the strength of the sheet; nylon 6 / EVOH provides certain heat resistance and has good barrier performance to non-polar organic solvents and non-polar gases and other gas gases, and also has excellent barrier properties to oxygen, nitrogen, hydrogen sulfide and other gases; the flame retardant makes the polymer waterproof board have excellent flame retardant performance; the toughening agent improves the softness and toughness of the sheet; the compatibilizer is a maleic anhydride type grafting agent (PE-g-MAH), because PE material and nylon material have poor compatibility, so it is necessary to intervene with a compatibilizer to improve the compatibility of the two and make the molecular distribution structure of the two A good layered distribution is formed, so that the sheet has good gas insulation performance; the modified additive helps the raw materials to be processed in twin-screw extrusion, thereby improving the output efficiency; the compounding effect of the antioxidant and the anti-ultraviolet agent greatly increases the weather resistance of the sheet, thereby extending the life of the sheet and helping to prevent the performance from decaying during short-term exposure and storage; the polymer waterproof board has good gas insulation, flame retardancy, antistatic properties and excellent mechanical properties. Even in the harsh use environment of long-term high and low temperature changes, it can still maintain good mechanical properties, gas insulation, flame retardancy and good antistatic properties, safe construction and long service life; and because the material has good mechanical properties, good flexibility, easy folding, road transportation and construction are very convenient, which can improve the efficiency of tunnel construction;

[0102] ② The antistatic polyethylene closed-cell foam board in the composite durable antistatic gas isolation system provided by the present invention can reduce the resistance of the foam board by filling it with highly conductive carbon black, which can reach 10 4 Ω, far lower than the national semi-conductive material (anti-static) 10 6 Ω requirement; adding dispersant can effectively reduce carbon black agglomeration, increase its dispersion in polyethylene, improve the resistance uniformity and consistency of foam board, and have a great effect on flow conduction; adding coupling agent, through the carbon black pre-treated with coupling agent, can make the ordinary inorganic carbon black chain segment grafted with organic segment, increase the stability and durability of carbon black in polyethylene foaming system, carbon black is not easy to migrate, and the continuous durability of conductive performance is greatly improved; antistatic polyethylene closed-cell foam board can effectively block most gas, and the permeability coefficient P≤10 -5 cm 3 cm / cm 2 ·s·Pa; and when used in the tunnel excavation process, it can eliminate the problem of static electricity accumulation on the primary lining structure and waterproof board, put an end to the phenomenon of concentrated discharge, and reduce the occurrence of accidents;

[0103] ③ The self-adhesive adhesive in the composite durable antistatic gas isolation system provided by the present invention, when applied to the isolation board, can fully adhere to the polymer waterproof board with the secondary lining structure, avoiding the occurrence of water leakage channels between the sprayed primary lining concrete structure mixed with air sealant and the secondary lining concrete structure mixed with air sealant, that is, it can avoid causing large-area leakage of the structure, so that the isolation board has good waterproof performance; and, because the waterproof board can be fully adhered to the secondary lining concrete structure mixed with air sealant, the accumulation of gas on the structural surface is reduced, the flow of gas is reduced, and the penetration pressure is reduced, which is of great help to the gas isolation system; in addition, by introducing the nitrogen-phosphorus halogen-free environmentally friendly flame retardant (FR562), the flame retardancy of the hot melt adhesive is significantly improved. When its content reaches 12%, the oxygen index is 31%, the vertical combustion grade can reach V0 level, and the flame retardancy reaches the "Combustion Performance Classification of Building Materials and Products" (GB / T 8624-2012), it is a flame-retardant material that can extinguish fire immediately and meet the requirements for tunnel fire safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0104] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0105] Figure 1 is a process flow chart for preparing a polymer waterproof board in step S1 of Example 1 to Example 7 of the present invention;

[0106] Figure 2 The effect of the introduction of PA6 / EVOH in the preparation of the polymer waterproof board in step S1 of Examples 1 to 7 of the present invention on the gas barrier properties of the polymer waterproof board;

[0107] Figure 3 The effect of the introduction of nitrogen-phosphorus halogen-free environmentally friendly flame retardant (MPP) during the preparation of the polymer waterproof board in step S1 of Examples 1 to 7 of the present invention on the flame retardant properties of the polymer waterproof board;

[0108] Figure 4 is a process flow chart of preparing a self-adhesive material in step S2 of Example 1 to Example 7 of the present invention;

[0109] Figure 5 The effect of the introduction of the nitrogen-phosphorus halogen-free environmentally friendly flame retardant (FR562) in step S2 of Examples 1 to 7 of the present invention on the flame retardancy of the self-adhesive material;

[0110] Figure 6Schematic diagram of the cross-sectional structure of the composite durable antistatic gas isolation system constructed in Examples 13 to 15 of the present invention.

[0111] In the figure: 1. primary lining concrete structure; 2. polyethylene closed-cell foam board; 3. isolation board; 31. polyurethane coating layer; 32. self-adhesive layer; 33. polymer waterproof board layer; 4. secondary lining concrete structure. DETAILED DESCRIPTION

[0112] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0113] 1. Preparation Example:

[0114] Ingredients:

[0115] The polyurethane coating used is Weidun, a single-component polyurethane waterproof coating Type I produced by Sichuan Hongyuan Waterproof Engineering Co., Ltd.; the airtight agent used is F511-B anti-seepage waterproof airtight agent produced by Sichuan Hongyuan Waterproof Engineering Co., Ltd.

[0116] Embodiment 1:

[0117] Preparation of non-asphalt-based self-adhesive gas insulation board (i.e., insulation board 3):

[0118] S1. Preparation of polymer waterproof board:

[0119] ① Raw materials, as shown in Table 1 below:

[0120] Table 1 Raw materials used in preparing polymer waterproof board in Example 1

[0121]

[0122] ②Preparation method:

[0123] A1. Raw material premixing: All raw materials are sucked into a high-speed mixer through a vacuum pump according to the proportion, and then dried in the high-speed mixer at a drying temperature of 53°C and a mixing time of 3 minutes. Then, the raw materials are mixed in a low-speed mixer for 5 minutes to ensure that the raw materials are evenly mixed.

[0124] A2, extrusion molding: the raw materials mixed evenly in step A1 are conveyed into a twin-screw extruder through a twin-screw conveyor, and the polymer waterproof board is extruded at an extrusion temperature of 220°C-240°C, and then the board is formed by a three-roll molding machine to a certain thickness and then cooled to room temperature;

[0125] A3, internal stress treatment: the polymer waterproof sheet formed in step A2 is pulled through the traction roller to the internal stress treatment section, and is tractioned through 4 groups of 80°C high temperature rollers and 4 groups of 10°C low temperature rollers for 4 cycles to treat and shape the sheet and eliminate the internal stress in the sheet;

[0126] A4, corona treatment: Place both ends of the polymer waterproof board after the internal stress treatment in step A3 under a voltage of 7KV for corona treatment, so as to form an oxidized polarization group on the surface of the polymer waterproof board, so that the surface of the waterproof board has polarity;

[0127] A5. Rolling up the coiled material: drying the polymer waterproof sheet after the corona treatment in step A4 at a temperature of 98° C. for 2 minutes; after cooling, pulling and rolling up the coiled material to obtain the polymer waterproof sheet;

[0128] S2. Preparation of self-adhesive material:

[0129] ① Raw materials, as shown in Table 2 below:

[0130] Table 2 Raw materials used in preparing self-adhesive materials in Example 1

[0131]

[0132] ②Preparation method:

[0133] B1. Liquid material feeding: the first polyisobutylene, the first C5 petroleum resin and the second C5 petroleum resin are weighed according to the proportion and put into the reaction kettle, and high-speed stirring is performed at a temperature of 100° C. for 20 minutes at a stirring speed of 8 Hz until they are uniformly mixed;

[0134] B2. Solid material feeding: SIS elastomer, second polyisobutylene, flame retardant, polyethylene wax, antioxidant and anti-ultraviolet agent are weighed according to the proportion and put into the reactor under high-speed stirring. The stirring speed of the high-speed stirring is 8 Hz, and the temperature is raised to 160° C. After the temperature rises to 160° C., stirring is continued for 40 minutes, and the stirring speed is continued at 4 Hz to obtain a hot melt adhesive;

[0135] B3, discharging and molding: the hot melt adhesive prepared in step B2 is passed through a 150-mesh filter screen to obtain a self-adhesive finished product, which is then packed into a packaging bag;

[0136] S3. Apply the self-adhesive material to the polymer waterproof board:

[0137] C1, hot melt box heating: the self-adhesive material prepared in step S2 is put into a hot melt box, and heated and melted by a step heating process of 155° C.-170° C. to obtain a molten adhesive material;

[0138] The step heating process is as follows: a hot melt box is provided with four temperature zones of 155°C, 160°C, 165°C and 170°C from top to bottom; the hot melt adhesive material loaded into the packaging bag is put into the hot melt box, the hot melt adhesive material first enters the 155°C temperature zone to start heating, the hot melt adhesive material flows down under the action of gravity, and is heated and melted in the 160°C temperature zone, the 165°C temperature zone and the 170°C temperature zone in turn to obtain a molten adhesive material;

[0139] C2, coating die coating: the molten adhesive obtained in step C1 is conveyed to the coating die of the hot melt box through the conveying channel in the hot melt box, and is evenly coated on the polymer waterproof board prepared in step S1 at a die temperature of 150° C., that is, a self-adhesive adhesive layer 32 is formed on the polymer waterproof board layer 33;

[0140] S4, applying polyurethane coating layer 31:

[0141] D1. Spray coating: spray the polyurethane coating on the self-adhesive layer 32 with a spray thickness of 0.2 mm;

[0142] D2. Drying: Dry the polymer waterproof board sprayed with polyurethane coating in step D1 at 60°C for 5 minutes to obtain a finished non-asphalt self-adhesive gas isolation board; the prepared non-asphalt self-adhesive gas isolation board: the polymer waterproof board layer 33 has a thickness of 1.2 mm; the self-adhesive layer 32 has a thickness of 0.8 mm; and the polyurethane coating layer 31 has a thickness of 0.15 mm.

[0143] Embodiment 2:

[0144] Preparation of non-asphalt-based self-adhesive gas insulation board (i.e., insulation board 3):

[0145] S1. Preparation of polymer waterproof board:

[0146] ① Raw materials, as shown in Table 3 below:

[0147] Table 3 Raw materials used in preparing polymer waterproof board in Example 2

[0148]

[0149] ②Preparation method:

[0150] A1. Raw material premixing: All raw materials are sucked into a high-speed mixer through a vacuum pump according to the proportion, and then dried in the high-speed mixer at a drying temperature of 50°C and a mixing time of 2 minutes. Then, the raw materials are mixed in a low-speed mixer for 6 minutes to ensure that the raw materials are evenly mixed.

[0151] A2, extrusion molding: the raw materials mixed evenly in step A1 are conveyed into a twin-screw extruder through a twin-screw conveyor, and the polymer waterproof board is extruded at an extrusion temperature of 220°C-240°C, and then the board is formed by a three-roll molding machine to a certain thickness and then cooled to room temperature;

[0152] A3, internal stress treatment: the polymer waterproof sheet formed in step A2 is pulled through the traction roller to the internal stress treatment section, and is circulated and pulled through 4 groups of 80°C high-temperature rollers and 4 groups of 10°C low-temperature rollers for 3 times to treat and shape the sheet and eliminate the internal stress in the sheet;

[0153] A4, corona treatment: Place both ends of the polymer waterproof board after the internal stress treatment in step A3 under a voltage of 7KV for corona treatment, so as to form an oxidized polarization group on the surface of the polymer waterproof board, so that the surface of the polymer waterproof board has polarity;

[0154] A5. Rolling up the coiled material: drying the polymer waterproof sheet after the corona treatment in step A4 at a temperature of 100° C. for 2 minutes; after cooling, pulling and rolling up the sheet to obtain the polymer waterproof sheet for the composite gas isolation board;

[0155] S2. Preparation of self-adhesive material:

[0156] ① Raw materials, as shown in Table 4 below:

[0157] Table 4 Raw materials used in preparing self-adhesive materials in Example 2

[0158]

[0159] ②Preparation method:

[0160] B1. Liquid material feeding: the first polyisobutylene, the first C5 petroleum resin and the second C5 petroleum resin are weighed according to the proportion and put into the reaction kettle, and high-speed stirring is performed at a temperature of 90° C. for 25 minutes at a stirring speed of 5 Hz until the mixture is uniformly mixed;

[0161] B2. Solid material feeding: SIS elastomer, second polyisobutylene, flame retardant, polyethylene wax, antioxidant and anti-ultraviolet agent are weighed according to the proportion and put into the reactor under high-speed stirring. The stirring speed of the high-speed stirring is 10 Hz, and the temperature is raised to 150° C. After the temperature rises to 150° C., stirring is continued for 45 minutes, and the stirring speed is continued at 3 Hz to obtain a hot melt adhesive;

[0162] B3, discharging and molding: the hot melt adhesive prepared in step B2 is passed through a 140-mesh filter to obtain a self-adhesive finished product, which is then packed into a packaging bag;

[0163] S3. Apply the self-adhesive material to the polymer waterproof board:

[0164] C1, hot melt box heating: the self-adhesive material prepared in step S2 is put into a hot melt box, and heated and melted by a step heating process of 155°C-170°C to obtain a molten adhesive material;

[0165] The step heating process is as follows: a hot melt box is provided with four temperature zones of 155°C, 160°C, 165°C and 170°C from top to bottom; the hot melt adhesive material loaded into the packaging bag is put into the hot melt box, the hot melt adhesive material first enters the 155°C temperature zone to start heating, the hot melt adhesive material flows down under the action of gravity, and is heated and melted in the 160°C temperature zone, the 165°C temperature zone and the 170°C temperature zone in turn to obtain a molten adhesive material;

[0166] C2, coating die coating: the molten adhesive in step C3 is conveyed to the coating die of the hot melt box through the conveying channel in the hot melt box, and is evenly coated on the polymer waterproof board prepared in step S1 at a die temperature of 150° C., that is, a self-adhesive adhesive layer 32 is formed on the polymer waterproof board layer 33;

[0167] S4, applying polyurethane coating layer 31:

[0168] D1. Spray coating: spray the polyurethane coating layer 31 onto the self-adhesive layer 32, with a spray thickness of 0.15 mm;

[0169] D2. Drying: Dry the polymer waterproof board sprayed with polyurethane coating in step D1 at a temperature of 55°C for 4.5 minutes to obtain a finished non-asphalt self-adhesive gas isolation board; the prepared non-asphalt self-adhesive gas isolation board: the thickness of the polymer waterproof board layer 33 is 1.2 mm; the thickness of the self-adhesive layer 32 is 0.8 mm; the thickness of the polyurethane coating layer 31 is 0.15 mm.

[0170] Embodiment 3:

[0171] Preparation of non-asphalt-based self-adhesive gas insulation board (i.e., insulation board 3):

[0172] S1. Preparation of polymer waterproof board:

[0173] ① Raw materials, as shown in Table 5 below:

[0174] Table 5 Raw materials used in preparing polymer waterproof board in Example 3

[0175]

[0176] ②Preparation method:

[0177] A1. Raw material premixing: All raw materials are sucked into a high-speed mixer through a vacuum pump according to the proportion, and then dried in the high-speed mixer at a drying temperature of 55°C and a mixing time of 4 minutes. Then, the raw materials are mixed in a low-speed mixer for 4 minutes to ensure that the raw materials are evenly mixed.

[0178] A2, extrusion molding: the raw materials mixed evenly in step A1 are conveyed into a twin-screw extruder through a twin-screw conveyor, and the polymer waterproof board is extruded at an extrusion temperature of 220°C-240°C, and then the board is formed by a three-roll molding machine to a certain thickness and then cooled to room temperature;

[0179] A3, internal stress treatment: the polymer waterproof sheet formed in step A2 is pulled through the traction roller to the internal stress treatment section, and is tractioned through 4 groups of 80°C high-temperature rollers and 4 groups of 10°C low-temperature rollers for 5 times to treat and shape the sheet and eliminate the internal stress in the sheet;

[0180] A4, corona treatment: Place both ends of the polymer waterproof board after the internal stress treatment in step A3 under a voltage of 7KV for corona treatment, so as to form an oxidized polarization group on the surface of the polymer waterproof board, so as to generate polarity on the surface of the polymer waterproof board;

[0181] A5. Rolling up the coiled material: drying the polymer waterproof sheet after the corona treatment in step A4 at a temperature of 95° C. for 2 minutes; after cooling, pulling and rolling up the coiled material to obtain the polymer waterproof sheet;

[0182] S2. Preparation of self-adhesive material:

[0183] ① Raw materials, as shown in Table 6 below:

[0184] Table 6 Raw materials used in preparing self-adhesive materials in Example 3

[0185]

[0186] ②Preparation method:

[0187] B1. Liquid material feeding: the first polyisobutylene, the first C5 petroleum resin and the second C5 petroleum resin are weighed according to the proportion and put into the reaction kettle, and high-speed stirring is performed at a temperature of 110° C. for 18 minutes at a stirring speed of 10 Hz until the mixture is uniformly mixed;

[0188] B1. Solid material feeding: SIS elastomer, second polyisobutylene, flame retardant, polyethylene wax, antioxidant and anti-ultraviolet agent are weighed according to the proportion and put into the reactor under high-speed stirring. The stirring speed of the high-speed stirring is 5 Hz, and the temperature is raised to 170° C. After the temperature rises to 170° C., stirring is continued for 35 minutes, and the stirring speed is continued at 5 Hz to obtain a hot melt adhesive;

[0189] B1. Discharging and molding: The hot melt adhesive prepared in step B2 is passed through a 160-mesh filter screen to obtain a self-adhesive finished product, which is then packed into a packaging bag;

[0190] S3. Apply the self-adhesive material to the polymer waterproof board:

[0191] C1, hot melt box heating: the self-adhesive material prepared in step S2 is put into a hot melt box, and heated and melted by a step heating process of 155°C-170°C to obtain a molten adhesive material;

[0192] The step heating process is as follows: a hot melt box is provided with four temperature zones of 155°C, 160°C, 165°C and 170°C from top to bottom; the hot melt adhesive material loaded into the packaging bag is put into the hot melt box, the hot melt adhesive material first enters the 155°C temperature zone to start heating, the hot melt adhesive material flows down under the action of gravity, and is heated and melted in the 160°C temperature zone, the 165°C temperature zone and the 170°C temperature zone in turn to obtain a molten adhesive material;

[0193] C2, coating die coating: the molten adhesive in step C3 is conveyed to the coating die of the hot melt box through the conveying channel in the hot melt box, and is evenly coated on the polymer waterproof board prepared in step S1 at a die temperature of 150° C., that is, a self-adhesive adhesive layer 32 is formed on the polymer waterproof board layer 33;

[0194] S4, applying polyurethane coating layer 31:

[0195] D1. Spray coating: spray the polyurethane coating layer 31 onto the self-adhesive layer 32, with a spray thickness of 0.2 mm;

[0196] D2. Drying: Dry the polymer waterproof board sprayed with polyurethane coating in step D1 at 65°C for 5.5 minutes to obtain a finished non-asphalt self-adhesive gas isolation board; the prepared non-asphalt self-adhesive gas isolation board: the polymer waterproof board layer 33 has a thickness of 2.0 mm; the self-adhesive layer 32 has a thickness of 0.3 mm; and the polyurethane coating layer 31 has a thickness of 0.2 mm.

[0197] Embodiment 4:

[0198] Preparation of non-asphalt-based self-adhesive gas insulation board (i.e., insulation board 3):

[0199] S1. Preparation of polymer waterproof board:

[0200] ① Raw materials, as shown in Table 7 below:

[0201] Table 7 Raw materials used in preparing polymer waterproof board in Example 4

[0202]

[0203] ② Preparation method: same as Example 1.

[0204] S2. Preparation of self-adhesive material:

[0205] ① Raw materials, as shown in Table 8 below:

[0206] Table 8 Raw materials used in preparing self-adhesive materials in Example 4

[0207]

[0208] ② Preparation method: same as Example 1.

[0209] S3. Applying the self-adhesive material to the polymer waterproof board: the preparation method is the same as that in Example 1.

[0210] S4. Applying a polyurethane coating layer 31: the preparation method is the same as that in Example 1.

[0211] Embodiment 5:

[0212] Preparation of non-asphalt-based self-adhesive gas insulation board (i.e., insulation board 3):

[0213] S1. Preparation of polymer waterproof board:

[0214] ① Raw materials, as shown in Table 9 below:

[0215] Table 9 Raw materials used in preparing polymer waterproof board in Example 5

[0216]

[0217] ② Preparation method: same as Example 1.

[0218] S2. Preparation of self-adhesive material:

[0219] ① Raw materials, as shown in 10 below:

[0220] Table 10 Raw materials used in preparing self-adhesive materials in Example 5

[0221]

[0222] ② Preparation method: same as Example 1.

[0223] S3. Applying the self-adhesive material to the polymer waterproof board: the preparation method is the same as that in Example 1.

[0224] S4. Applying a polyurethane coating layer 31: the preparation method is the same as that in Example 1.

[0225] Embodiment 6:

[0226] Preparation of non-asphalt-based self-adhesive gas insulation board (i.e., insulation board 3):

[0227] S1. Preparation of polymer waterproof board:

[0228] ① Raw materials, as shown in Table 11 below:

[0229] Table 11 Raw materials used in preparing polymer waterproof board in Example 6

[0230]

[0231] ② Preparation method: same as Example 1.

[0232] S2. Preparation of self-adhesive material:

[0233] ① Raw materials, as shown in Table 12 below:

[0234] Table 12 Raw materials used in preparing self-adhesive materials in Example 6

[0235]

[0236] ② Preparation method: same as Example 1.

[0237] S3. Applying the self-adhesive material to the polymer waterproof board: the preparation method is the same as that in Example 1.

[0238] S4. Applying a polyurethane coating layer 31: the preparation method is the same as that in Example 1.

[0239] Embodiment 7:

[0240] Preparation of non-asphalt-based self-adhesive gas insulation board (i.e., insulation board 3):

[0241] S1. Preparation of polymer waterproof board:

[0242] ① Raw materials, as shown in Table 13 below:

[0243] Table 13 Raw materials used in preparing polymer waterproof board in Example 7

[0244]

[0245] ② Preparation method: same as Example 1.

[0246] S2. Preparation of self-adhesive material:

[0247] ① Raw materials, as shown in Table 14 below:

[0248] Table 14 Raw materials used in preparing self-adhesive materials in Example 7

[0249]

[0250] ② Preparation method: same as Example 1.

[0251] S3. Applying the self-adhesive material to the polymer waterproof board: the preparation method is the same as that in Example 1.

[0252] S4. Applying a polyurethane coating layer 31: the preparation method is the same as that in Example 1.

[0253] Embodiment 8:

[0254] Preparation of antistatic polyethylene closed-cell foam board 2:

[0255] ① Raw materials, as shown in Table 15 below:

[0256] Table 15 Raw materials used in preparing antistatic polyethylene closed-cell foam board 2 in Example 8

[0257]

[0258] ②Preparation method:

[0259] (1) Preliminary mixing of solid materials: linear low-density polyethylene, high-conductive carbon black, high-density polyethylene, and foaming agent are weighed according to the proportion and put into a mixer for the first preliminary mixing. The solid materials are mixed at a temperature of 50° C. for 5 minutes and mixed evenly.

[0260] (2) Blending of additives: After weighing the coupling agent, cross-linking agent, dispersant, stabilizer, antioxidant and anti-ultraviolet agent according to the proportion, add them into the mixer for secondary blending, and mix them at a temperature of 50° C. for 10 minutes to obtain a uniformly mixed formula material;

[0261] (3) Extrusion molding: The mixed formula material in step (2) is conveyed into a twin-screw through a twin-screw spiral riser, and an antistatic polyethylene closed-cell foam sheet 2 is extruded at an extrusion temperature of 190° C. to 210° C., and then the sheet is formed into a fixed thickness by a three-roll molding machine and then cooled to room temperature;

[0262] (4) corona treatment: placing both ends of the antistatic polyethylene closed-cell foam board 2 treated in step (3) under a voltage of 7 kV for corona treatment, so as to form an oxidized polarization group on the surface of the antistatic polyethylene closed-cell foam board 2, thereby generating polarity on the surface of the antistatic polyethylene closed-cell foam board 2;

[0263] (5) Coil winding: The antistatic polyethylene closed-cell foam board 2 after corona treatment is dried and cooled, and then pulled and rolled.

[0264] Embodiment 9:

[0265] Preparation of antistatic polyethylene closed-cell foam board 2:

[0266] ① Raw materials, as shown in Table 16 below:

[0267] Table 16 Raw materials used in preparing antistatic polyethylene closed-cell foam board 2 in Example 9

[0268]

[0269] ②Preparation method:

[0270] (1) Preliminary mixing of solid materials: linear low-density polyethylene, high-conductive carbon black, high-density polyethylene, and foaming agent are weighed according to the proportion and put into a mixer for the first preliminary mixing. The materials are mixed at a temperature of 45° C. for 6 minutes and mixed evenly;

[0271] (2) Blending of additives: After weighing the coupling agent, cross-linking agent, dispersant, stabilizer, antioxidant and anti-ultraviolet agent according to the proportion, add them into the mixer for secondary blending, and mix them at a temperature of 45° C. for 12 minutes to obtain a uniformly mixed formula material;

[0272] (3) Extrusion molding: The mixed formula material in step (2) is conveyed into a twin-screw through a twin-screw spiral riser, and an antistatic polyethylene closed-cell foam sheet 2 is extruded at an extrusion temperature of 190° C. to 210° C., and then the sheet is formed into a fixed thickness by a three-roll molding machine and then cooled to room temperature;

[0273] (4) corona treatment: placing both ends of the antistatic polyethylene closed-cell foam board 2 treated in step (3) under a voltage of 7 kV for corona treatment, so as to form an oxidized polarization group on the surface of the antistatic polyethylene closed-cell foam board 2, thereby generating polarity on the surface of the antistatic polyethylene closed-cell foam board 2;

[0274] (5) Coil winding: The antistatic polyethylene closed-cell foam board 2 after corona treatment is dried and cooled, and then pulled and rolled.

[0275] Embodiment 10:

[0276] Preparation of antistatic polyethylene closed-cell foam board 2:

[0277] ① Raw materials, as shown in Table 17 below:

[0278] Table 17 Raw materials used in preparing antistatic polyethylene closed-cell foam board 2 in Example 10

[0279]

[0280] ②Preparation method:

[0281] (1) Preliminary mixing of solid materials: linear low-density polyethylene, high-conductive carbon black, high-density polyethylene, and foaming agent are weighed according to the proportion and put into a mixer for the first preliminary mixing. The materials are mixed at a temperature of 55° C. for 4 minutes and mixed evenly;

[0282] (2) Blending of additives: After weighing the coupling agent, cross-linking agent, dispersant, stabilizer, antioxidant and anti-ultraviolet agent according to the proportion, add them into the mixer for secondary blending, and mix them at a temperature of 55° C. for 12 minutes to obtain a uniformly mixed formula material;

[0283] (3) Extrusion molding: The mixed formula material in step (2) is conveyed into a twin-screw through a twin-screw spiral riser, and an antistatic polyethylene closed-cell foam sheet 2 is extruded at an extrusion temperature of 190° C. to 210° C., and then the sheet is formed into a fixed thickness by a three-roll molding machine and then cooled to room temperature;

[0284] (4) corona treatment: placing both ends of the antistatic polyethylene closed-cell foam board 2 treated in step (3) under a voltage of 7 kV for corona treatment, so as to form an oxidized polarization group on the surface of the antistatic polyethylene closed-cell foam board 2, thereby generating polarity on the surface of the antistatic polyethylene closed-cell foam board 2;

[0285] (5) Coil winding: The antistatic polyethylene closed-cell foam board 2 after corona treatment is dried and cooled, and then pulled and rolled.

[0286] Embodiment 11:

[0287] Preparation of antistatic polyethylene closed-cell foam board 2:

[0288] ① Raw materials, as shown in Table 18 below:

[0289] Table 18 Raw materials used in preparing antistatic polyethylene closed-cell foam board 2 in Example 11

[0290]

[0291] ② Preparation method: same as Example 8.

[0292] Embodiment 12:

[0293] Preparation of antistatic polyethylene closed-cell foam board 2:

[0294] ① Raw materials, as shown in Table 19 below:

[0295] Table 19 Raw materials used in preparing antistatic polyethylene closed-cell foam board 2 in Example 12

[0296]

[0297] ② Preparation method: same as Example 8.

[0298] Embodiment 13:

[0299] like Figure 6 As shown: The specific steps of constructing the composite durable antistatic gas isolation system of the present invention are:

[0300] (1) spraying a primary lining concrete structure 1 with a content of 0.2% F511-B anti-seepage waterproof airtight agent on the rock protection structure, the thickness of the primary lining concrete structure 1 is 12 cm;

[0301] (2) gluing the polyethylene closed-cell foam board 2 prepared in Example 8 onto the primary lining concrete structure 1;

[0302] (3) The isolation board 3 prepared in Example 1 is fixedly laid on the polyethylene closed-cell foam board 2 by a hanging method or a concealed nail ring;

[0303] (4) A secondary lining concrete structure 4 with a content of 0.2% F511-B anti-seepage, waterproof and airtight agent is sprayed on the isolation board 3. The thickness of the secondary lining concrete structure 4 is 45 cm.

[0304] Embodiment 14:

[0305] like Figure 6 As shown: The specific steps of constructing the composite durable antistatic gas isolation system of the present invention are:

[0306] (1) spraying a primary lining concrete structure 1 with a content of 0.2% F511-B anti-seepage waterproof airtight agent on the rock protection structure, the thickness of the primary lining concrete structure 1 is 10 cm;

[0307] (2) gluing the polyethylene closed-cell foam board 2 prepared in Example 9 onto the primary lining concrete structure 1;

[0308] (3) The isolation board 3 prepared in Example 2 is fixedly laid on the polyethylene closed-cell foam board 2 by a hanging method or a concealed nail ring;

[0309] (4) A secondary lining concrete structure 4 containing 0.2% F511-B anti-seepage, waterproof and airtight agent is sprayed on the isolation board 3. The thickness of the secondary lining concrete structure 4 is 50 cm.

[0310] Embodiment 15:

[0311] like Figure 6 As shown: The specific steps of constructing the composite durable antistatic gas isolation system of the present invention are:

[0312] (1) spraying a primary lining concrete structure 1 with a content of 0.2% F511-B anti-seepage waterproof airtight agent on the rock protection structure, the thickness of the primary lining concrete structure 1 is 15 cm;

[0313] (2) gluing the polyethylene closed-cell foam board 2 prepared in Example 10 onto the primary lining concrete structure 1;

[0314] (3) The isolation board 3 prepared in Example 3 is fixedly laid on the polyethylene closed-cell foam board 2 by a hanging method or a concealed nail ring;

[0315] (4) A secondary lining concrete structure 4 with a doping amount of 0.2% F511-B anti-seepage, waterproof and airtight agent is sprayed on the isolation board 3. The thickness of the secondary lining concrete structure 4 is 40 cm.

[0316] 2. Performance testing:

[0317] 1. The mechanical properties and weather resistance of the polymer waterproof board prepared in step S1 of Example 1 to Example 7 were tested according to TB / T 3360.1-2014. The results are shown in Tables 20 and 21 below:

[0318] Table 20 Mechanical properties of polymer waterproof boards prepared in Examples 1 to 7

[0319]

[0320] Table 21 Weathering properties of polymer waterproof boards prepared in Examples 1 to 7

[0321]

[0322] As can be seen from Table 20, the polymer waterproof boards prepared in Examples 1 to 7 have excellent strength, good toughness and excellent waterproofness, and all indicators meet the existing TB / T 3360.1-2014 standards. Due to the good mechanical properties and softness, the simplicity of material construction is guaranteed and the construction efficiency is improved.

[0323] It can be seen from Table 21 that the polymer waterproof boards prepared in Examples 1 to 7 have high temperature resistance and excellent anti-aging properties. Therefore, even in harsh environments for a long time, they can still maintain good mechanical properties and have a long service life.

[0324] 2. The adhesive properties of the self-adhesive materials prepared in step S2 of Example 1 to Example 7 were tested according to GB / T23457-2017. The results are shown in Table 22 below:

[0325] Table 22 Adhesive properties of self-adhesive materials obtained in Examples 1 to 7

[0326]

[0327] As can be seen from Table 22, the bonding strength of the self-adhesive materials prepared in Examples 1 to 7 is higher than the GB / T 23457-2017 standard, and the bonding performance is still very good after heat treatment, water immersion treatment and ultraviolet treatment. When preparing the gas isolation board 3, it can form good adhesion with the polymer waterproof board and the functional coating.

[0328] 3. The performance of the non-asphalt-based self-adhesive gas isolation board (i.e., isolation board 3) prepared in Examples 1 to 7 was tested. The results are shown in Table 23 below:

[0329] Table 23 Properties of the isolation board 3 obtained in Examples 1 to 7

[0330]

[0331] 4. The properties of the antistatic polyethylene closed-cell foam board 2 prepared in Examples 8 to 12 were tested. The results are shown in Table 24 below:

[0332] Table 24 Properties of the antistatic polyethylene closed-cell foam board 2 prepared in Example 8-Example 12

[0333] resistance Gas permeability coefficient Example 1 <![CDATA[1×10 4 Oh]]> <![CDATA[P≤1×10 -5 cm 3 ·cm / cm 2 ·s·Pa]]> Example 2 <![CDATA[1×10 4 Oh]]> <![CDATA[P≤1×10 -5 cm 3 ·cm / cm 2 ·s·Pa]]> Example 3 <![CDATA[1×10 4 Oh]]> <![CDATA[P≤1×10 -5 cm 3 ·cm / cm 2 ·s·Pa]]> Example 4 <![CDATA[1×10 4 Oh]]> <![CDATA[P≤1×10 -5 cm 3 ·cm / cm 2 ·s·Pa]]> Example 5 <![CDATA[1×10 4 Oh]]> <![CDATA[P≤1×10 -5 cm 3 ·cm / cm 2 ·s·Pa]]>

[0334] 3. Experimental example:

[0335] 1. The introduction of nylon 6 / EVOH significantly improves the gas barrier properties of polymer waterproof sheets. The gas barrier tester is used to test the gas barrier properties using the differential pressure method. The specific results of the experiment are as follows: Figure 2 As shown:

[0336] Depend on Figure 2 It can be seen that due to the introduction of nylon 6 / EVOH, the gas barrier performance of the polymer waterproof board is significantly improved, especially for composite gas, including but not limited to H2S / CH4 / SO2 / CO2 / N2 / C2H6 / C3H8 / O2 / O3. With the increase of nylon 6 / EVOH, the gas barrier performance first improves and then remains unchanged. Therefore, when the nylon 6 / EVOH content is 20%, nylon 6 / EVOH has no performance gain. When nylon 6 / EVOH reaches 20%, the gas barrier performance is the best, and the gas permeability coefficient reaches P≤1×10 -15 cm 3 cm / cm 2 ·s·Pa conditions.

[0337] The permeability coefficient of H2S gas is P≤1×10 -16 cm 3 cm / cm 2 ·s·Pa;

[0338] The CH4 gas permeability coefficient reaches P≤1×10 -15 cm 3 cm / cm 2 ·s·Pa;

[0339] The gas permeability coefficient of N2 reaches P≤1×10 -18 cm 3 cm / cm 2 ·s·Pa;

[0340] O2 gas permeability coefficient reaches P≤1×10 -20 cm 3 cm / cm 2 ·s·Pa;

[0341] The permeability coefficients of other gases are all P≤1×10 -16 cm 3 cm / cm 2 ·s·Pa.

[0342] 2. The introduction of nitrogen-phosphorus halogen-free environmentally friendly flame retardant (MPP) significantly improves the flame retardancy of polymer waterproof board. The specific results of the experiment are as follows: Figure 3 As shown:

[0343] Depend on Figure 3 It can be seen that the introduction of nitrogen-phosphorus halogen-free environmentally friendly flame retardant (MPP) can significantly improve the flame retardancy of polymer waterproof board. When its content reaches 20%, the oxygen index is 30%, the vertical combustion level can reach V0 level, and the flame retardant level reaches the B1 fire protection level in the "Classification of Combustion Performance of Building Materials and Products" (GB / T 8624-2012). It is a flame-retardant material and can be extinguished as soon as it is away from fire, which can meet the requirements of tunnel fire safety.

[0344] 3. The introduction of nitrogen-phosphorus halogen-free environmentally friendly flame retardant (FR562) has significantly improved the flame retardancy of self-adhesive materials. The specific results of the experiment are as follows: Figure 5 As shown:

[0345] Depend on Figure 5 It can be seen that through the introduction of nitrogen-phosphorus halogen-free environmentally friendly flame retardant (FR562), the flame retardancy of the self-adhesive material has been significantly improved. When its content reaches 12%, the oxygen index is 31%, the vertical combustion level can reach V0 level, and the flame retardancy level reaches the B1 fire protection level in the "Classification of Combustion Performance of Building Materials and Products" (GB / T 8624-2012). It is a flame-retardant material and can be extinguished as soon as it is away from the fire, which can meet the use requirements of tunnel fire safety.

[0346] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A composite durable antistatic gas isolation system, characterized by: The invention comprises a primary lining concrete structure mixed with air sealant, an antistatic polyethylene closed-cell foam board, an isolation board, and a secondary lining concrete structure mixed with air sealant in sequence; wherein the primary lining concrete structure mixed with air sealant is arranged on a side close to gas; the isolation board is a gas isolation board or a non-asphalt-based self-adhesive gas isolation board; The antistatic polyethylene closed-cell foam board is prepared from the following raw materials in percentage by weight: Linear low-density polyethylene 70.7%-85.6%; Highly conductive carbon black 5%-10%; High-density polyethylene 5%-10%; Foaming agent 1%-2%; Crosslinking agent 1%-2%; Dispersant 0.3%-0.8%; Coupling agent 0.1%-0.5%; Stabilizer 0.5%-1%; Antioxidant 1%-1.5%; Anti-ultraviolet agent 0.5%-1.5%; The sum of the weight percentages of each raw material is 100%; The method for preparing the non-asphalt-based self-adhesive gas isolation board comprises the following steps: S1. Preparation of polymer waterproof board: A1. Raw material premixing: All raw materials are sucked into the high-speed mixer through a vacuum pump according to the proportion, and then dried in the high-speed mixer for 2-4 minutes. Then, the raw materials are put into the low-speed mixer for 4-6 minutes until the raw materials are evenly mixed. A2, extrusion molding: the raw materials mixed evenly in step A1 are conveyed into a twin-screw extruder through a twin-screw conveyor, and the gas isolation board polymer waterproof board is extruded at an extrusion temperature of 220°C-240°C, and then the board is formed by a three-roll molding machine to a certain thickness and then cooled to room temperature; A3, internal stress treatment: the polymer waterproof sheet formed in step A2 is pulled through the traction roller to the internal stress treatment section, and is circulated through 4 groups of 80°C high-temperature rollers and 4 groups of 10°C low-temperature rollers for 3-5 times to treat and shape the sheet and eliminate the internal stress in the sheet; A4, corona treatment: Place both ends of the polymer waterproof board after internal stress treatment in A2 under 7KV voltage for corona treatment, forming oxidized polarization groups on the surface of the polymer waterproof board, so that the surface of the waterproof board produces polarity; A5. Coil rolling: The polymer waterproof board with internal stress eliminated in step A3 is dried, cooled, pulled and rolled up to obtain a finished polymer waterproof board; S2. Preparation of self-adhesive material: B1. Liquid material feeding: weigh the first polyisobutylene, the first C5 petroleum resin and the second C5 petroleum resin according to the ratio and put them into the reactor, and stir them at a high speed at a temperature of 90°C-110°C for 18min-25min until they are evenly mixed; B2. Solid material feeding: SIS elastomer, second polyisobutylene, flame retardant, polyethylene wax, antioxidant and anti-ultraviolet agent are weighed according to the proportion and put into the reaction kettle under high-speed stirring, and the temperature is raised to 150-170°C at the same time. After the temperature rises to 150-170°C, continue stirring for 35-45 minutes to obtain hot melt adhesive; B3, discharging and molding: after the hot melt adhesive prepared in step B2 passes through a filter screen, a self-adhesive finished product in the state of hot melt adhesive is obtained, and the finished product is put into a packaging bag; S3. Apply the self-adhesive material to the polymer waterproof board: C1. Hot melt box heating: put the hot melt adhesive in the packaging bag into the hot melt box, and heat and melt it through a step heating process of 155℃-170℃ to obtain molten adhesive; C2, coating die coating: the molten adhesive in step C3 is conveyed to the coating die of the hot melt box through the conveying channel in the hot melt box, and is evenly coated on the polymer waterproof board prepared in step S1 at a die temperature of 150° C., that is, a self-adhesive layer is formed on the polymer waterproof board layer; S4. Apply polyurethane coating layer: D1. Spray coating: Spray the polyurethane coating layer on the self-adhesive layer with a spray thickness of 0.15mm-0.2mm; D2. Drying: Dry the polymer waterproof board sprayed with polyurethane coating in step D1 at a temperature of 55° C.-65° C. for 4.5 min-5.5 min to obtain a finished product of a non-asphalt-based self-adhesive gas isolation board.

2. The composite durable antistatic gas isolation system according to claim 1 is characterized in that: The raw materials for preparing the antistatic polyethylene closed-cell foam board include: The foaming agent is azodicarbonamide; The cross-linking agent is DCP; The dispersant is vinyl bisstearamide; The coupling agent is a silane coupling agent; The antioxidant comprises the following raw materials in parts by weight: 0.5 to 1 part of tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentyl alcohol; 0.5 part of tris(2,4-di-tert-butylphenyl) phosphite; The anti-ultraviolet agent comprises the following raw materials in parts by weight: ultraviolet absorber: 0.2-0.7 parts; hindered amine light stabilizer: 0.3-0.8 parts.

3. The composite durable antistatic gas isolation system according to claim 2 is characterized in that: The preparation method of the antistatic polyethylene closed-cell foam board comprises the following steps: (1) Preliminary mixing of solid materials: weigh linear low-density polyethylene, high-conductive carbon black, high-density polyethylene, and foaming agent according to the proportion, and put them into a mixer for the first preliminary mixing. Mix the materials at a temperature of 45°C-55°C for 4-6 minutes until they are evenly mixed. (2) Blending of additives: After weighing the coupling agent, cross-linking agent, dispersant, stabilizer, antioxidant and UV inhibitor according to the proportion, add them into the mixer for secondary blending. Mix the materials at a temperature of 45°C-55°C for 8min-12min until they are evenly mixed to obtain a uniformly mixed formula material. (3) Extrusion molding: The uniformly mixed formula material in step (2) is conveyed into a twin-screw through a twin-screw spiral riser, and an antistatic polyethylene closed-cell foam sheet is extruded at an extrusion temperature of 190°C-210°C, and then the sheet is formed into a fixed thickness by a three-roll molding machine and then cooled to room temperature; (4) Coil winding: The antistatic polyethylene closed-cell foam board after corona treatment is dried, cooled, and then pulled and rolled.

4. The composite durable antistatic gas isolation system according to claim 1 is characterized in that: The isolation board is a gas isolation board or a non-asphalt-based self-adhesive gas isolation board. The permeability coefficient of the gas isolation board is ≤1×10 -15 cm 3 cm / cm 2 ·s·Pa; The air permeability coefficient of the non-asphalt-based self-adhesive gas isolation board is ≤1×10 -16 cm 3 cm / cm 2 ·s·Pa.

5. The composite durable antistatic gas isolation system according to claim 4 is characterized in that: The non-asphalt-based self-adhesive gas isolation board includes a polymer waterproof board layer, a self-adhesive layer and a polyurethane coating layer; the polymer waterproof board layer is the bottom layer, the self-adhesive layer covers the polymer waterproof board layer, and the polyurethane coating layer is the surface layer.

6. The composite durable antistatic gas isolation system according to claim 5, characterized in that: The polymer waterproof board in the polymer waterproof board layer is prepared from the following raw materials in weight percentage: Linear low density polyethylene 25%-50% Nylon 6 / EVOH 10%-30% High-density polyethylene 5%-10%; Toughening agent 5%-15%; Flame retardant 10%-20%; Compatibilizer 1%-6%; Modification additives 1%-2%; Antioxidant 1%-1.5%; Anti-ultraviolet agent 0.5%-1.5%; The sum of the weight percentages of the various raw materials is 100%.

7. The composite durable antistatic gas isolation system according to claim 6 is characterized in that: The self-adhesive material in the self-adhesive material layer is prepared from the following raw materials in weight percentage: SIS elastomer 18%-21%; The first polyisobutylene is 10%-18%; The second polyisobutylene is 6%-8%; First, C5 petroleum resin 25%-30%; The second C5 petroleum resin 5%-12%; Flame retardant 10%-20%; Polyethylene wax 2%-5%; Antioxidant 1%-1.5%; Anti-ultraviolet agent 0.5%-1.5%; The sum of the weight percentages of each raw material is 100%; in, The first polyisobutylene is a low molecular weight polyisobutylene; The second polyisobutylene is a high molecular weight polyisobutylene; The first C5 petroleum resin is aliphatic C5; The second C5 petroleum resin is an aliphatic C5 hydrogenated petroleum resin.

8. The composite durable antistatic gas isolation system according to claim 7 is characterized in that: The raw materials for preparing the polymer waterproof board include: The vinyl molar equivalent content in the nylon 6 / EVOH barrier material is not less than 44%, and the weight ratio of nylon to EVOH is 5:5; The toughening agent comprises the following raw materials in parts by weight: 5-10 parts of polyolefin thermoplastic elastomer; 0-5 parts of thermoplastic ethylene-propylene rubber; The flame retardant is a nitrogen-phosphorus halogen-free environmentally friendly flame retardant; The compatibilizer is a maleic anhydride type grafting agent; The modification aid comprises the following raw materials in parts by weight: polyethylene wax: 0.5-1 part; vinyl bisstearamide: 0.3-0.8 part; white oil: 0.2 part; The antioxidant comprises the following raw materials in parts by weight: 0.5 to 1 part of tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentyl alcohol; 0.5 part of tris(2,4-di-tert-butylphenyl) phosphite; The anti-ultraviolet agent comprises the following raw materials in parts by weight: ultraviolet absorber: 0.2-0.7 parts; hindered amine light stabilizer: 0.3-0.8 parts; The raw materials for preparing the self-adhesive material include: The flame retardant is a nitrogen-phosphorus halogen-free environmentally friendly flame retardant; The toughening agent includes the following raw materials in parts by weight: The antioxidant includes the following raw materials in parts by weight: 0.5 to 1 part of tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentyl alcohol; 0.5 part of tris(2,4-di-tert-butylphenyl) phosphite; The anti-ultraviolet agent comprises the following raw materials in parts by weight: ultraviolet absorber: 0.2-0.7 parts; hindered amine light stabilizer: 0.3-0.8 parts.

9. The method for constructing a composite durable antistatic gas isolation system according to any one of claims 1 to 8, characterized in that: The steps include: (1) Spray the primary lining concrete structure on the rock protection structure. The thickness of the primary lining concrete structure is 10cm-15cm; (2) Gluing antistatic polyethylene closed-cell foam board to the primary lining concrete structure; (3) Use the suspension method or concealed nailing ring to fix the isolation board on the anti-static polyethylene closed-cell foam board; In the isolation board: the thickness of the polymer waterproof board layer is 1.2mm-2.0mm; the thickness of the self-adhesive layer is 0.3mm-0.8mm; the thickness of the polyurethane coating layer is 0.15mm-0.2mm; (4) Spray a secondary lining concrete structure on the isolation board. The thickness of the secondary lining concrete structure is 40cm-50cm.

Citation Information

Patent Citations

  • Wide application hot-melt pressure sensitive adhesive for HDPE self-adhesive coiled material and preparation method thereof

    CN103361012A

  • Reverse-adhesion waterproof board

    CN106285727A

  • Gas-proof method for area grouting combined with anti-seepage and protecting in process of tunnel passing through coal bed

    CN107083973A

  • Composite durable antistatic gas isolation system

    CN212614739U

  • Electrically conductive polyethylene

    CN85109427A